Prawo zakładowe — in rebus angustis? wybrane problemy administracyjnoprawne - Lisowski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The aim of the paper is to point to the key problems concerning the legislation and validity of administrative establishment law. It has been demonstrated that these problems stem from the discrepancies between various doctrinal and normative interpretations of the status of these forms of activity of administration. They are also connected with the constitutionality of the existence of the acts of administrative establishment law and the issues of their publication, as well as the direct judicial review of such acts.
Keywords: administrative establishment law; administrative law